THE DEVELOPMENT OF ADDED VALUE CHAIN IN LIVESTOCK (British Journal of Global Ecology and Sustainable Development, 2023)
Animal husbandry has been a crucial aspect of human civilization. It involves the care and breeding of animals for various purposes, including food, fiber, and companionship. Over the years, the animal husbandry industry has undergone significant changes, with advancements in technology and research leading to the creation of added-value products. This paper examines the development of added-value products in animal husbandry, analyzing how they have contributed to increased profits and sustainability in the industry.